Effects of waterway regulation structures on the planktonic community in the upper Yangtze River - Yu Wan; Guiquan Huang; Hongbo Du; Shengfa Yang; Wei Yang; Wenjie Li (Ecological Indicators, 2023)
To investigate the effects of the waterway regulation structures on the hydraulic characteristics, water physicochemical factors, and the planktonic community in the upper Yangtze River, this study was conducted in August and September of 2022 on two ecological dikes in the Chongqing section of the upper Yangtze River: the longitudinal dike and the spur dike. High-throughput sequencing technology was used to explore the differences in planktonic community structures upstream and downstream of the waterway regulation structures during the dry season, as well as their main influencing factors. The results showed that the dissolved oxygen increased significantly, and the turbidity and flow rate decreased significantly in downstream of dikes. The spur dike exhibited more pronounced changes in water quality and hydrodynamic factors compared to the longitudinal dike. The diversity index of phytoplankton, zooplankton, and fungi in the downstream of dikes were higher than those in the upstream, and the bacterial diversity index was higher than those of eukaryotes at each sampling site. The impact of the spur dike on the planktonic biodiversity index was greater than that of the longitudinal dike, as it alters flow velocity, turbidity, and dissolved oxygen. The major phyla of phytoplankton, zooplankton, and bacteria, including Cryptophyta (70.37–80.57 %), Mollusca (7.56–37.50 %), and Proteobacteria (48.53–55.92 %), had a higher relative abundance in upstream of dike, and their relative abundance in spur dike was higher than that in longitudinal dike. In contrast, the relative abundance of the major phylum of fungi, Ascomycota (37.15–56.85 %), showed an opposite trend in both dike-to-dike comparison and dike upstream-to-downstream comparison to the above three plankton. The analysis of the neutral community model indicated that the predominance of stochastic assembly processes in the planktonic community was higher in the longitudinal dike compared to the spur dike, and longitudinal dike demonstrated higher rates of planktonic migration and speciation compared to the spur dike. Flow rate, dissolved oxygen, and turbidity were the significance influencing factors on the planktonic community structure in the aquatic environment around dike. Differences in dike-related environmental factors result in greater interactions among prokaryotes in the spur dike, while eukaryotes exhibited a more complex network of relationships in the longitudinal dike. These findings can provide a theoretical basis for the protection of biodiversity and the construction of ecological waterways in the waterway regulation engineering area.